Potential misidentifications of two climate indicator species of the marine arctic ecosystem: Calanus glacialis and C. finmarchicus - Gabrielsen, Tove M; Merkel, Benjamin; Søreide, Janne; Johansson-Karlsson, Emma; Bailey, Allison; Vogedes, Daniel Ludwig; Nygård, Henrik Andreas; Varpe, Øystein; Berge, Jørgen (Polar Biology, 2012)
Calanoid copepods of the genus Calanus represent an important, nutrient-rich food source for a multitude of Arctic marine organisms. Although morphologically very similar, their life histories and ecological roles differ. Because the distribution of Calanus glacialis and C. finmarchicus corresponds to Arctic and Atlantic water masses, respectively, they are regularly used as climate indicators. A correct identification of these species is therefore necessary in many ecological, environmental and climatological studies. In this study, we aimed at validating the traditionally used morphological characteristics (combining prosome length and copepodite stage) for separation of species of Calanus by using molecular tools (PCR–RFLP of the 16S mtDNA). A total of 418 specimens of copepodite stages CIV, CV and CVI(af) from three Arctic fjords have been identified both morphologically and genetically. We find that the morphological identification systematically overestimates the abundance of C. finmarchicus at the expense of C. glacialis. Hence, parts of the C. glacialis populations are found to be structurally smaller and the within population size range thus larger than previously assumed. Consequently, using the traditional morphological species delimitation poses a serious problem in the use of these two species as indicators of Atlantic versus Arctic water masses and thus as climatic indicators. Furthermore, it obscures our understanding of the life history differences between the two species and of their relative importance as food for a number of ecologically and economically important species in the Arctic.